Fungal osteomyelitis with vertebral re-ossification. (2016) - O′Guinn, Devon J.; Serletis, Demitre; Kazemi, Noojan
Highlights: Fungal osteomyelitis is a rare entity in the spectrum of spinal infections. We present a case of spinal osteomyelitis secondary to Blastomyces dermatitides . Infectious lytic lesions of the spine, when stable, may be managed conservatively. In rare instances, vertebral re-ossification may occur with conservative management. Abstract: Introduction: We present a rare case of thoracic vertebral osteomyelitis secondary to pulmonary Blastomyces dermatitides . Presentation of case: A 27-year-old male presented with three months of chest pains and non-productive cough. Examination revealed diminished breath sounds on the right. CT/MR imaging confirmed a right-sided pre-/paravertebral soft tissue mass and destructive lytic lesions from T2 to T6. CT-guided needle biopsy confirmed granulomatous pulmonary Blastomycosis. Conservative management with antifungal therapy was initiated. Neurosurgical review confirmed no clinical or profound radiographic instability, and the patient was stabilized with TLSO bracing. Serial imaging 3 months later revealed near-resolution of the thoracic soft tissue mass, with vertebral re-ossification from T2 to T6. Discussion: Fungal osteomyelitis presents a rare entity in the spectrum of spinal infections. In such cases, lytic spinal lesions are classically seen in association with a large paraspinous mass. Fungal infections of the spinal column may be treated conservatively, with surgical intervention reserved for progressive cases manifesting with neurological compromise and/or spinal column instability. Here, we found unexpected evidence for vertebral re-ossification across the affected thoracic levels (T2-6) in response to IV antibiotic therapy and conservative bracing, nearly 3 months later.